Proyecto de factibilidad para la creación de una empresa procesadora de bolos en el cantón el Empalme, provincia del Guayas, año 2012 - Peñafiel Zambrano, María Ramona (2012)
The investigation for the feasibility of creation of a micro company process of skittles was carried out it in the canton El Empalme. This arose of ideas of business to take advantage of the geographical and climatic conditions of this important canton of Ecuador, located to 167 km. of Guayaquil, to the northeast of the county of the Guayas, their limits are: for the west, north and this, demarcations interprovincial among Guayas, Manabí and The Ríos, it Possesses a pleasant tropical climate with minimum temperatures 21°C and maxim 26°C, their precipitation averages yearly it is of 1600 - 3200mm. Inhabitants' number 74.451 and their extension is of 3.695 Km2. The formulation of the problem constituted the starting point of the present investigation; do let us wonder objectively Of what way it impacts the creation of the micro company process of skittles, in the demand of the inhabitants of the canton El Empalme; to solve it plantié like general objective to carry out the study of feasibility for the creation of a company process of Skittles at El Empalme, province of Guayas, and as specific objectives: 1) to develop the phase of market study, being focused in the offer and unsatisfied demand of the product, 2) to Make the studies technician and economic for the creation of the company process of skittles, and, 3) to Establish the financial evaluation of the project. With the purpose of fulfilling the objectives outlined work presently, the methods were used: Investigative, analytic, scientific, synthetic and inductive-deductive; the applied investigation types were bibliographical and of field specifically because he/she was carried out in the place of the facts, they were used technical of investigation for the taking of qualitative information, by means of focus groups and quantitative through the sampling carried out to population's segment understood among the ages from 10 to 59 years of the canton El Empalme, with obtained results of the 397 carried out surveys. Outstanding data were gathered on the development of the project, deepening the investigation in the study of feasibility and their three components of understanding analysis: of market, technician and financial; whose obtained results constitute the support base for the investor, so that he/she makes their best decision. He was defined the profitability of the project with the application of the following formulas: total costs, balance point (PE), box flows, net current value (they GO), it appraises it interns of return (TIR), depreciation of active, relationship benefits cost (R. B/C) and analysis of sensibility. When concluding the investigation I can conclude that: The market study demonstrated that in the canton El Empalme 2'052.400 units of skittles are offered, available in stores, trade, bars of educational institutions and traveling salespersons to a price of $0,10 for unit. Regarding the demand a potential was determined it calculates unsatisfied of 13'235.755 equivalent to 86,34%; with what is justified the size of the project, same it will allow to cover among the 11.78 and 14.81% of the future demand projected for the period 2012 - 2016. Quantified between1'806.000 and 2'457.043 units/year. The investment among active fixed and differed it ascends to the quantity of 101.622,63 dollars with a contribution of the investor of 45% and the requirement of projected financial leverage of 55%. The fixed costs $67.604,22 and the variables $29.121,57. The revenues in the first year are of 117.390,00 dollars. The box flow generated in the first year is of 36.092,58 dollars. The balance point in the first year corresponds to the production and sale of 1'383.204 units/year. The relationship benefits cost it is 2,05; the VAN 114.964,58 and the equivalent TIR to 43%. The project is also sensitive since it supports a decrease in sales of until 11% or an increment in its production costs of until 15%. It causes an impact on the employment generating 11 new work squares. << ALONE SHE HAS TO BE ABLE TO WHO HAS THE CAPACITY TO MAKE >>